Dreamcatcher [videorecording (Blu-Ray)] - Kasdan, Lawrence, 1949-; Goldman, William, 1931-2018; Freeman, Morgan; Jane, Thomas; Lee, Jason, 1970-; King, Stephen, 1947- (Warner Bros. Entertainment, Inc., 2014)
Four friends with an unusual power become stranded in a blizzard and are confronted by a deadly alien force. As they try to stop this unparalleled horror, the fate of the world is in their hands. This title has been Repackaged.